"Everything is connected": On the Relevance of an Integral Understanding of Reality in Laudato Si'. (June 2016) - Marx, Reinhard Cardinal
The encyclical Laudato Si' calls for a deep reading, for its consistent message that "everything is connected" leads to a fundamental questioning of several operating assumptions for modern societies, economies, politics, and ways of life. Fundamentally, the encyclical calls into question the model of progress that has been presumed in the modern age. The new idea of progress put forth in this encyclical presumes the connectedness of all things, and offers a way forward toward solving the ecological crisis. But this cannot happen apart from ecological conversion and a new way of seeing our place in the world.